An alternative eukaryotic DNA excision repair pathway. - Freyer, G A (1995)
DNA lesions induced by UV light, cyclobutane pyrimidine dimers, and (6-4)pyrimidine pyrimidones are known to be repaired by the process of nucleotide excision repair (NER). However, in the fission yeast Schizosaccharomyces pombe, studies have demonstrated that at least two mechanisms for excising UV photo-products exist; NER and a second, previously unidentified process. Recently we reported that S. pombe contains a DNA endonuclease, SPDE, which recognizes and cleaves at a position immediately adjacent to cyclobutane pyrimidine dimers and (6-4)pyrimidine pyrimidones. Here we report that the UV-sensitive S. pombe rad12-502 mutant lacks SPDE activity. In addition, extracts prepared from the rad12-502 mutant are deficient in DNA excision repair, as demonstrated in an in vitro excision repair assay. DNA repair activity was restored to wild-type levels in extracts prepared from rad12-502 cells by the addition of partially purified SPDE to in vitro repair reaction mixtures. When the rad12-502 mutant was crossed with the NER rad13-A mutant, the resulting double mutant was much more sensitive to UV radiation than either single mutant, demonstrating that the rad12 gene product functions in a DNA repair pathway distinct from NER. These data directly link SPDE to this alternative excision repair process. We propose that the SPDE-dependent DNA repair pathway is the second DNA excision repair process present in S. pombe.